Implementing Cold-Start Reduction Techniques on Globus Compute - Lembo, João Gabriel; Goldman, Alfredo (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD); 2025: Anais do XXVI Simpósio em Sistemas Computacionais de Alto DesempenhoDO - 10.5753/sscad.2025.16692, 2025)
This work addresses the cold-start delay issue within Globus Compute, a FaaS solution aimed at scientific workflows. We introduce the Warm-Start Engine, a novel engine for the system which integrates two techniques: an increase in the keepalive time of resources and a new task assignment algorithm. To validate our approach, we conducted a comparative performance analysis of the original system against two new versions, one with only the extended keepalive time and another with both modifications. The results demonstrate that the Warm-Start Engine reduces total workflow execution times by up to 62% and improves individual function execution times by as much as 82%, when compared to the baseline Globus Compute implementation.